Marketing Strategies For Improving Brand Awareness: A Case of Kitanata Ruang - Bella Ganjar Priscila Ganjar; Asep Taryana; Siti Jahroh (School of Business, IPB University (SB-IPB), 2023)
There is a furniture MSME that has just entered the furniture industry, namely KitaNata Ruang. KitaNata Ruang is present amid competition in the industry with an unknown brand. The purpose of this researchs to provide a marketing mix strategy to increase KitaNata Ruang brand awareness. The research method used is the 4C marketing mix, brand awareness pyramid, SWOT matrix, and QSP matrix. The results of the study show an evaluation of the marketing mix using the 4C marketing mix, co-creation elements in the form of a lack of product feel, currency in the form of providing price variations, communal activation in the form of programs for partners, and conversations is more active dissemination of information. The level of brand awareness of KitaNata Ruang is in the position of brand recognition for potential consumers and brand recall for actual consumers. Formulation of strategies using the SWOT matrix produced alternative strategies with strategic priority orders using the QSP matrix, active in marketing promotions through digital creators, service and product innovation, expanding business with resellers or partners, implementing membership features, bundling, and sales promotions, active in the exhibition furniture industry, using augmented reality and virtual reality technology and improving information processing. Keywords: brand awareness, furniture, marketing mix, QSPM, SWOT